Innovation as A Strategy of Agrowical Competition Advantage in Improving Marketing Performance of Luwak Coffee Products in Gianyar Bali - Pande Ketut Ribek; I Gede Rihayana (International Journal of Applied Business and International Management, 2019)
Agro tourism is a place for nature-based creativity and packaged in the form of trips or tourism activities to plantations or agriculture. One of them is luwak coffee agro tourism. This agrotourism has an icon of luwak coffee as a mainstay product in attracting tourists and increasing sales. Through a study entitled "Innovation concept as a strategy in argrowisata in improving marketing performance of luwak coffee product in Bali. The purpose of this research is to know the variables that become the power, weaknesses, opportunities and threats in the face of Luwak coffee agro tourism in marketing its products. Engineering data collection done by using the method of interviewing, observation, and documentation. Whereas technical analysis using IE and SWOT matrix. From the results of research in the know agro-tourism Luwak coffee has strength (Strength), namely: innovation is technically in producing quality products with options, change the design in accordance with the wishes of the customer, developed ideas and systems change the distribution. In addition, the completeness of facilities, special rates, service, location, employee appearance, the mastery of a foreign language. While his weakness (Weakness) lack of promotion of the maximum, and the lack of mastery of the technology in the production of goods. Opportunity (Opportunity) of environmental external in the show by the Bali security stability indicators conducive, local government policy that is flexible, the rate of inflation, the bargaining power of buyers. While the threats (Treats) agro-tourism growth rates, the influx of newcomers the same products, the existence of goods substitution that can replace the product, the competition is fellow companies in the industry, the existence of the bargaining power of buyers. Performance marketing in doing that is to improve the quality of the product, promotion, price adjustment, intense, best service with distribution system fast, innovation.